Deep learning assisted diagnosis system: improving the diagnostic accuracy of distal radius fractures - Zhang, Jiayao; Li, Zhimin; Lin, Heng; Xue, Mingdi; Wang, Honglin; Fang, Ying; Liu, Songxiang; Huo, Tongtong; Zhou, Hong; Yang, Jiaming; Xie, Yi; Xie, Mao; et al. (Frontiers in Medicine, 2023)
Objectives: To explore an intelligent detection technology based on deep learning algorithms to assist the clinical diagnosis of distal radius fractures (DRFs), and further compare it with human performance to verify the feasibility of this method. Methods: A total of 3240 patients (fracture: n=1620, normal: n=1620) were included in this study, with a total of 3276 wrist joint anteroposterior (AP) X-ray films (1639 fractured, 1637 normal) and 3260 wrist joint lateral X-ray films (1623 fractured, 1637 normal). We divided the patients into training set, validation set and test set in a ratio of 7:1.5:1.5. The deep learning models were developed using the data from the training and validation sets, and then their effectiveness were evaluated using the data from the test set. Evaluate the diagnostic performance of deep learning models using receiver operating characteristic (ROC) curves and area under the curve (AUC), accuracy, sensitivity, and specificity, and compare them with medical professionals. Results: The deep learning ensemble model had excellent accuracy (97.03%), sensitivity (95.70%), and specificity (98.37%) in detecting DRFs. Among them, the accuracy of the AP view was 97.75%, the sensitivity 97.13%, and the specificity 98.37%; the accuracy of the lateral view was 96.32%, the sensitivity 94.26%, and the specificity 98.37%. When the wrist joint is counted, the accuracy was 97.55%, the sensitivity 98.36%, and the specificity 96.73%. In terms of these variables, the performance of the ensemble model is superior to that of both the orthopedic attending physician group and the radiology attending physician group. Conclusions: This deep learning ensemble model has excellent performance in detecting DRFs on plain X-ray films. Using this artificial intelligence model as a second expert to assist clinical diagnosis is expected to improve the accuracy of diagnosing DRFs and enhance clinical work efficiency.